INVOLVEMENT IN THE ACTIVITIES OF ILLEGAL ORGANIZATIONS AS A LINGUISTIC PROBLEM - Bozhenkova, Natalia; Katyshev , Pavel; Afanaseva, Elmira; Saakyan, Levon (Revista Inclusiones, 2020)
The study of human involvement in the activities of illegal organizations as a social phenomenon is conducted within the framework of an integrated multilateral expertise, since such involvement is an interdisciplinary category. Experience reveals that the use of linguistic analysis to prove verbal violations in communication within illegal groups implies an expanded understanding of the category of involvement. In this regard, the methods of critical discourse analysis are especially relevant, since they are based on the language motivation system and meet the requirements of social and cognitive suprasystems. The ultimate goal of the study is to present expert evidence of organized criminal activity in court, according to which the authors formulate the main principles of characterizing involvement based on an analytical review of the phenomenon of participation in interactive sociolinguistics (John J. Gumperz), discourse analysis (Wallace Chafe, Deborah Tannen) and communicative ethnography (Niko Besnier)